2017
DOI: 10.1177/2396987317695140
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction in persons with severe stroke – A longitudinal report from the Sunnaas International Network (SIN) stroke study

Abstract: Introduction: The overall aim of the present study was to explore perceived life satisfaction in persons with stroke, from admission to specialised rehabilitation until follow up 1 year post-discharge. The secondary aim was to evaluate possible external and internal explanatory factors for perceived life satisfaction. Patients and methods: A prospective, descriptive study of specialised rehabilitation of persons with stroke. Persons with a primary diagnosis of stroke were enrolled in the study. Results: Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…There is a high preva lence of sexual problems and dysfunction among stroke survivors and their partners (7)(8)(9). A previous multina tional study, conducted within the same research net work as the present study, found that patients reported their sexual life to be one of the most dissatisfactory areas in life (10,11), confirming the need for sexual rehabilitation after stroke. Patients often do not raise questions about sexuality as they feel embarrassed, and those patients may want their healthcare providers to raise the topic (12)(13)(14)(15).…”
supporting
confidence: 81%
“…There is a high preva lence of sexual problems and dysfunction among stroke survivors and their partners (7)(8)(9). A previous multina tional study, conducted within the same research net work as the present study, found that patients reported their sexual life to be one of the most dissatisfactory areas in life (10,11), confirming the need for sexual rehabilitation after stroke. Patients often do not raise questions about sexuality as they feel embarrassed, and those patients may want their healthcare providers to raise the topic (12)(13)(14)(15).…”
supporting
confidence: 81%
“…Family caregivers of stroke survivors experience a heavy burden and a low life satisfaction . The heavy burden of caregiver not only affects caregivers' physical and psychological health, life satisfaction, and quality of life but also determines the quality of caring and quality of life for stroke survivors .…”
Section: Introductionmentioning
confidence: 99%
“…LiSat is frequently used to assess life satisfaction in studies of persons with stroke (5,(11)(12)(13)(14)(15)(16). Despite this, there is limited knowledge about the reliability of LiSat.…”
mentioning
confidence: 99%